Feasibility of apalutamide combined with androgen deprivation therapy and short-course low-dose prednisone in treating metastatic hormone-sensitive prostate cancer: a pilot randomized controlled trial - Yang, Dingyuan; Chen, Wenqiang; Lai, Fei; Qiu, Mingxing; Li, Jun (Frontiers in Oncology, 2023)
The role of prednisone in the prevention of androgen receptor antagonist-related rash and treatment for metastatic hormone-sensitive prostate cancer (mHSPC) is unclear. This trial (ChiCTR2200060388) aimed to investigate the feasibility of apalutamide combined with androgen deprivation therapy (ADT) and short-course low-dose prednisone in the treatment of mHSPC. All patients received apalutamide and ADT and were randomly divided into two groups based on the administration of oral prednisone or not (control group). The primary endpoint was the incidence of rash. The secondary endpoint included proportion of patients with decline in PSA ≥50% from baseline, PSA ≥90% from baseline, and decreased to PSA ≤0.2 ng/mL. Between June 2021 and March 2022, a total of 83 patients were enrolled (41 in the prednisone group and 42 in the control group). During the 6-month follow-up, the incidence of rash was significantly lower in the prednisone group compared with the control group (17.1% vs. 38.1%, P=0.049). There were no significant differences in the incidence of other adverse events, number of patients who required dose adjustment (reduction, interruption, or discontinuation) of apalutamide due to rash, number of patients with prostate specific antigen (PSA) decrease ≥50%, number of patients with PSA decrease ≥90%, and number of patients with PSA ≤0.2 ng/mL between the two groups. In patients with mHSPC, the addition of short-course low-dose prednisolone to apalutamide plus ADT can reduce the incidence of rash without risk of other adverse events.